Recovery from an unexpected standing-slip in professional ballet dancers - Simpkins, C.; Ahn, J.; Shin, S.; Yang, F. (Journal of Biomechanics, 2022)
Although interventional studies have suggested that dance-based training may reduce fall risk for older adults based on unperturbed assessments, it remains unknown whether dance (particularly ballet) enhances recovery from an external perturbation. This preliminary study sought to test if and how ballet dancers respond differently to a novel standing-slip perturbation relative to non-dancers. Ten young professional ballet dancers and 10 age/sex-matched non-dancers were exposed to an unannounced slip while standing on the treadmill. Their reactions to the slip, characterized by dynamic gait stability (primary outcome), and the recovery stepping and trunk movements (secondary outcomes), were compared between groups. No significant group difference in dynamic gait stability was found at slip onset and recovery step liftoff, but dancers were more stable than non-dancers at touchdown (p = 0.046). Compared to non-dancers, dancers took a longer (p = 0.049) and faster (p = 0.007) backward recovery step and exhibited a less backward leaned trunk at all instants (p = 0.026). Our study suggests that professional ballet dancers are more stable after a novel standing-slip than non-dancers. This better slip-related fall resistance among dancers could result from their more effective recovery stepping strategy and better trunk movement control after the slip. Both reactions may be attributed to ballet training, which requires frequent backward stepping and an upright trunk. Our findings could potentially provide preliminary evidence for applying ballet training to reduce balance losses and falls in people at a high fall risk. More studies are needed to examine ballet training`s effects among other populations with elevated fall risk in real-life situations.